Analyzing the Korean Diaspora: A case study of Koryo-saram and Sakhalin Koreans - Jung, Hyogyeong
Koryo-saram i Sachalin Koreańczycy to etniczni Koreańczycy mieszkający w krajach postsowieckich. W artykule tym stara się wyjaśnić pojęcia dotyczące tych Koreańczyków etnicznych w krajach posowieckich poprzez teorię diaspor i przeanalizować je dalej z koncepcją „koreańskiej diaspory” i „miejsca diaspory”. W badaniu wykorzystano metodę „porównania z małym N” i „studium przypadku”, dokonując przeglądu literatury koreańskiej, rosyjskiej i angielskiej. Analizując diasporę sowiecko-koreańską poprzez ramy „kraj-gospodarza-społeczeństwo międzynarodowe” z aspektami politycznymi, gospodarczymi i społecznymi, wizualizuje się „miejsce diaspory”. Koryo-saram and Sakhalin Koreans are ethnic Koreans living in the post-Soviet countries. This paper tries to clarify the terminology regarding these ethnic Koreans in the post-Soviet countries through the diaspora theory, and analyze them further with the concept of the ‘Korean diaspora’ and ‘the place of diaspora’. The research took Small-N comparison and case study method by reviewing Korean, Russian, and English literature. By analysing the Soviet Korean diaspora through ‘homeland-host country-international society’ framework with political, economic and social aspects, ‘the place of diaspora’ is visualised.